The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1175/jhm-d-21-0134.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Classification of Flash Drought Events Reveals Distinct Classes of Forcings and Impacts

Abstract: Recent years have seen growing appreciation that rapidly intensifying “flash droughts” are significant climate hazards with major economic and ecological impacts. This has motivated efforts to inventory, monitor, and forecast flash drought events. Here we consider the question of whether the term “flash drought” comprises multiple distinct classes of event, which would imply that understanding and forecasting flash droughts might require more than one framework. To do this, we first extend and evaluate a soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…For most CONUS areas (Figure 3), EDFD has a low TPR prior to SMPD onset which supports the findings by Osman et al. (2022) showing that one pathway for SMPD development has no ED early warning signal and is referred to as a low severity “stealth” FD which is forced by precipitation deficits, whereas the other two potential pathways do contain excessive ED prior to drought onset. ED has potential for overestimation on the impact of crop yields because RZSM is not explicitly accounted for (Rigden et al., 2020), but research has identified that RZSM and ED co‐regulate stomatal conductance and plant stress is induced under high ED conditions despite having concurrent, high RZSM conditions (F. Zhang et al., 2021; J. Zhang et al., 2021).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For most CONUS areas (Figure 3), EDFD has a low TPR prior to SMPD onset which supports the findings by Osman et al. (2022) showing that one pathway for SMPD development has no ED early warning signal and is referred to as a low severity “stealth” FD which is forced by precipitation deficits, whereas the other two potential pathways do contain excessive ED prior to drought onset. ED has potential for overestimation on the impact of crop yields because RZSM is not explicitly accounted for (Rigden et al., 2020), but research has identified that RZSM and ED co‐regulate stomatal conductance and plant stress is induced under high ED conditions despite having concurrent, high RZSM conditions (F. Zhang et al., 2021; J. Zhang et al., 2021).…”
Section: Discussionsupporting
confidence: 85%
“…The Evaporative Demand Drought Index (EDDI) identifies anomalous ED leading to surface moisture limitations and this index found similar interannual drought patterns as the United States Drought Monitor (USDM), evaporative stress index (ESI), and standardized precipitation index (SPI), and EDDI was able to identify drought development up to 2 months prior to the USDM (Hobbins et al., 2016; McEvoy et al., 2016). Research has identified three potential pathways for FD development which describe antecedent environmental conditions prior to FD onset and these pathways are dry & demanding, evaporative, or stealth (Osman et al., 2022). Both dry and demanding and evaporative FD pathways contain elevated ED prior to drought development, suggesting the potential use of EDDI as an early warning of FD events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But overall, we find that soil moisture conditions converge rather than diverge in the period leading up to and through the heat maximum (Table 1)—perhaps because the drought had already driven moisture conditions so low—such that there is no clear indication that this increase in evaporative demand triggered a cascading drought‐heat‐drought feedback. We note that this result might not hold when severe heatwaves hit more humid regions or when there is not already a severe drought; indeed, some types of rapid‐onset “flash droughts” are understood to be triggered by elevated air temperatures (Osman et al., 2022).…”
Section: Resultsmentioning
confidence: 92%
“…Apart from the conditions occurring during the event, examinations of antecedent meteorological conditions leading to flash drought onset have received less attention (e.g. Ford and Labosier 2017, Osman et al 2022). This knowledge gap, combined with climate warming-which intensifies the flash drought occurrence (Wang et al 2016, Yuan et al 2019, Shah et al 2022increases the potential of future impacts.…”
Section: Introductionmentioning
confidence: 99%